2020
DOI: 10.1097/gme.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high protein, low-glycemic index diet on lean body mass, strength, and physical performance in late postmenopausal women: a randomized controlled trial

Abstract: Objective: To investigate whether increasing protein consumption to twice the recommended daily allowance (RDA) by The Institute of Medicine affects lean body mass (LBM), muscle strength, and physical performance in late postmenopausal women. Methods: Parallel-group randomized trial with 26 apparently healthy women aged ≥ 65 years. Participants were randomly assigned to low-glycemic index diets with protein consumption at current RDA (0.8 g/kg body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…As participantes perderam em média 4% de peso corporal, 3% de gordura e 2% de massa magra. Em estudo realizado comparando o consumo de dietas de baixo índice glicêmico e um grupo com dieta de baixo índice glicêmico combinado com proteína excedendo a Ingestão Diária Recomendada (RDA), encontrou-se que o consumo proteico maior do que o definido pela RDA não contribuiu para maior manutenção de tecidos magros, sendo o consumo recomendo suficiente para perda de peso e mínima perda de massa magra 11 .…”
Section: Osunclassified
“…As participantes perderam em média 4% de peso corporal, 3% de gordura e 2% de massa magra. Em estudo realizado comparando o consumo de dietas de baixo índice glicêmico e um grupo com dieta de baixo índice glicêmico combinado com proteína excedendo a Ingestão Diária Recomendada (RDA), encontrou-se que o consumo proteico maior do que o definido pela RDA não contribuiu para maior manutenção de tecidos magros, sendo o consumo recomendo suficiente para perda de peso e mínima perda de massa magra 11 .…”
Section: Osunclassified
“…In fact, a Cochrane systematic review including data from 202 overweight or obese men and women in six RCTs reported a significantly greater decrease in total FM in the low GI diet than in control diet groups [ 42 ]. Specifically in postmenopausal women, a clinical trial with low GI (<55) dietary intervention, aimed to balance energy needs, has shown that, despite similar energy intake and resting metabolic rates during the six months of follow-up, all participants lost total body and regional FM [ 43 ].…”
Section: Dietary Intake and Clinical Endpoints In Menopausal Womenmentioning
confidence: 99%
“… 94 It has been also observed that protein intake exceeding the RDA (1.6gr/kg/d vs 0.8gr/kg/d) did not increase LBM, strength, and physical performance in a sample of late postmenopausal woman consuming a low-glycemic index diet for 6 months. 95 In addition, when combined with a resistance exercise training during 10 weeks, authors concluded that in postmenopausal women, an increased on protein intake (1.2gr/kg/d) did not promote higher lean body mass gain when compared to RDA recommendation. 92 But others reported that in postmenopausal women, even a moderate increase in protein intake (~1.2 g protein·kg-1·d-1) when combined to 10 weeks of resistance exercise, could promote a small additional improvement in functional capacity but not in strength and lean mass.…”
Section: Introductionmentioning
confidence: 98%
“… 97 Finally, at long term (5-year follow-up), it appears that high protein intake (1.2g/kg/d) is associated with beneficial effects on muscle mass and size and bone mass in elderly women. 95 …”
Section: Introductionmentioning
confidence: 99%